2012
DOI: 10.1155/2012/956814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Two Intense Dust Storms on Aerosol Characteristics and Radiative Forcing over Patiala, Northwestern India

Abstract: Impact of dust storms on the aerosol characteristics and radiative forcing over Patiala, northwestern India has been studied during April-June of 2010 using satellite observations and ground-based measurements. Six dust events (DE) have been identified during the study period with average values of Aqua-MODIS AOD 550 and Microtops-II AOD 500 over Patiala as 1.00 ± 0.51 and 0.84 ± 0.41, respectively while Aura-OMI AI exhibits high values ranging from 2.01 to 6.74. TheÅngström coefficients α 380−870 and β range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 82 publications
(111 reference statements)
2
47
0
Order By: Relevance
“…Some studies had quantified RF caused by dust storms over the Indian subcontinent. For example Sharma et al (2012) calculated RF over Patiala in India for 6 days of high dust loading (τ 500 = 1 ± 0.51) and found the average RF to vary between −50 and −100 W m −2 at surface level and −10 and −25 W m −2 at TOA. In another study Prasad et al (2007) calculated RF over Kanpur, India, and found the average RF at surface level to be to increase from −30 W m −2 for March to −84 W m −2 for June whereas net RF at TOA increased from −3.2 W m −2 for March to 43 W m −2 for June (ω 500 ≈ 0.84-0.74, τ 500 ≈ 0.55-1.18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies had quantified RF caused by dust storms over the Indian subcontinent. For example Sharma et al (2012) calculated RF over Patiala in India for 6 days of high dust loading (τ 500 = 1 ± 0.51) and found the average RF to vary between −50 and −100 W m −2 at surface level and −10 and −25 W m −2 at TOA. In another study Prasad et al (2007) calculated RF over Kanpur, India, and found the average RF at surface level to be to increase from −30 W m −2 for March to −84 W m −2 for June whereas net RF at TOA increased from −3.2 W m −2 for March to 43 W m −2 for June (ω 500 ≈ 0.84-0.74, τ 500 ≈ 0.55-1.18).…”
Section: Discussionmentioning
confidence: 99%
“…A lot of ground-based and airborne measurement campaigns mainly in the African, Mediterranean and Asian regions have been conducted in recent years to analyze the optical and physical properties of dust aerosols (Sabbah et al, 2001;Ahn et al, 2007;Heinold et al, 2008;Kaskaoutis et al, 2008;McConnell et al, 2008;Osborne et al, 2008;Ansmann et al, 2011;Haywood et al, 2011), the frequency of dust outbreaks (Goudie and Middleton, 1992;Gao et al, 2003;Kutiel andFruman 2003, Rezazadeh et al, 2013) and their sources and transport range (Youlin et al, 2002;El-Askary et al, 2003, Washington et al, 2003Xuana et al, 2004;Tsolmon et al, 2008;Rashki et al, 2012;Notaro et al, 2013). Several case studies of dust outbreaks have been conducted in which direct radiative forcing at the surface and at top of the atmosphere (TOA) have been calculated using ground-based and satellite-based data (Xu et al, 2003;Costa et al, 2006;Prasad et al, 2007;Di Sarra et al, 2008;Markowicz et al, 2008;Pandithurai et al, 2008;Di Biagio et al, 2010;Lemaître et al, 2010;Park et al, 2010;Sharma et al, 2012). The results are highly variable depending on their regional and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…The industrial cities like Ludhiana, Mandi Gobindgarh located in the northwest direction of the sampling site affect the aerosol characteristics over the study region. For further detail related to the site description, reference is made to our earlier publications (Rajput et al, 2011;Sharma et al, 2012;Singh et al, 2014). This site represents a region where both anthropogenic and natural aerosols show distinct seasonal characteristics and mixing.…”
Section: Site Description and Meteorologymentioning
confidence: 99%
“…In autumn, the large scale post harvest paddy residue burning in and around the city is a major source of pollutants (Mittal et al, 2009). During spring and summer, the region experiences occasional dust storms (Sikka, 1997;Sharma et al, 2012). In May during summer, wheat residue burning also contributes significantly to ambient PM (Rajput et al, 2011).…”
Section: Site Description and Meteorologymentioning
confidence: 99%
See 1 more Smart Citation